Characterization of H5N1 Influenza Virus Variants with Hemagglutinin Mutations Isolated from Patients - Watanabe, Yohei (mBio, 2015)
A change in viral hemagglutinin (HA) receptor binding specificity from α2,3- to α2,6-linked sialic acid is necessary for highly pathogenic avian influenza (AI) virus subtype H5N1 to become pandemic. However, details of the human-adaptive change in the H5N1 virus remain unknown. Our database search of H5N1 clade 2.2.1 viruses circulating in Egypt identified multiple HA mutations that had been selected in infected patients. Using reverse genetics, we found that increases in both human receptor specificity and the HA pH threshold for membrane fusion were necessary to facilitate replication of the virus variants in human airway epithelia. Furthermore, variants with enhanced replication in human cells had decreased HA stability, apparently to compensate for the changes in viral receptor specificity and membrane fusion activity. Our findings showed that H5N1 viruses could rapidly adapt to growth in the human airway microenvironment by altering their HA properties in infected patients and provided new insights into the human-adaptive mechanisms of AI viruses.